Exploring the Use of Minecraft Education Edition to Support Computational Thinking, Coding Skills, and AI Literacy: A Case Study in an Indonesian Madrasah Informatics Classroom - Meiningdias, Catur Yoga; Suryaman, Maman; Wahyudin, Undang Ruslan (Akademika : Jurnal Teknologi Pendidikan, 2025)
This study investigates how Minecraft Education Edition can support digital transformation in the Informatics curriculum of an Indonesian Islamic senior high school (madrasah). It examines how game-based learning mediates the development of computational thinking, coding fluency, and foundational artificial intelligence (AI) literacy, as well as the affective qualities of the learning environment. A qualitative case study was conducted at MAN 9 Jakarta with 210 Grade 10 students organised into six Informatics classes, one Informatics teacher, and the madrasah principal. Data were collected through classroom observations of Minecraft-based lessons, semi-structured interviews with 30 focal students (five representatives from each class), interviews with the teacher and principal, and documentation of student artefacts and institutional reports. Thematic analysis followed an iterative process of coding, data display, and conclusion drawing, supported by triangulation, member checking, and an audit trail to enhance trustworthiness. The findings show substantial gains in computational thinking: students articulated decomposition strategies, recognised patterns across missions, mentally simulated algorithms, and engaged in systematic debugging. Coding proficiency improved as learners used sequences, conditionals, and loops to design solutions in authentic missions. Emerging AI literacy was evident when students described agents as rule-based systems and attributed errors to flawed code rather than autonomous intent. The Minecraft-based environment fostered joyful, mindful, and meaningful engagement, characterised by high motivation, sustained focus, and perceived relevance to real-world applications. The study concludes that Minecraft Education provides an effective, contextually appropriate model for Informatics instruction in madrasah settings, with implications for curriculum design, teacher professional development, and SDG-oriented digital transformation policies.